Pleural infection caused by Legionella anisa. - Bornstein, N (1989)
The first case of infection caused by Legionella anisa with isolation of the organism is reported here. The presence of L. anisa in the water supply of the hospital and the isolation of this species in the pleural fluid of a patient suffering from nosocomial pleurisy confirm the potential pathogenicity of this Legionella species.